A fragments mass distribution scaling relations for fragmenting shells with variable thickness subjected to internal explosive loading. (October 2018) - Zhang, Zhibiao; Huang, Fenglei; Cao, Yuan; Yan, Cheng
Highlights: The first study of the mass distribution scaling relations for fragments from shells with variable thickness subjected to internal explosive loading. The morphology, fracture mode and mass distribution of the fragments from shells with variable thickness were systemically presented for the first time. The characteristic mass for the fragments is smaller when the shell with variable thickness and same structure is initiated from the large end. The shell produces longer fragments for initiation from the small end. The semi-empirical equations for scaling relations for the fragments' mass distribution were established. Abstract: This paper presents scaling relations of the fragments mass distribution for fragmenting shell with variable thickness subjected to internal explosive loading. Available formulas usually predict the fragmentation law of shell with constant thickness, and there are few sources that describe the fragment mass distribution of shells with variable thickness, which are usually used in the Earth Penetration Warhead (EPW). In the study, shells with variable thickness fragmentation were investigated experimentally, and the fragment mass distribution was obtained by statistical analysis. Furthermore, the semi-empirical scaling relations between the fragments' mass statistical characteristic value of shells with variable thickness and the physical parameters based on the Mott statistical distribution and Grady formula is proposed by the theoretical analysis and data analysis. The position of the initiation end and the taper of the variable thickness shell are considered in the scaling relations which has wider applicability in the study of the fragments mass distribution of shells with variable thickness subjected to internal explosive loading.